2017
DOI: 10.1136/bcr-2017-220799
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem encephalitis and acute polyneuropathy associated with hepatitis E infection

Abstract: A 59-year-old man presented with feverish illness. His Glasgow Coma Scale was 15, had reduced visual acuity in the left eye with partial left ptosis and mild left hemiparesis with an extensor left plantar. Over 48 hours, he accrued multiple cranial nerves palsies and progressed to a flaccid paralysis necessitating admission to an intensive care unit.Cerebrospinal fluid (CSF) study showed 20 lymphocytes and raised protein. Viral and bacterial PCRs were negative. Samples for Lyme, blood-borne viruses, syphilis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…HEV RNA was detectable in the HEV-replicated sites, including the liver, spleen, kidneys, intestines, brain, and uterus, and this result stably confirmed the extrahepatic replication sites of HEV. HEV replication has recently been identified in the kidneys (Geng et al, 2015;Pischke et al, 2017), brain (Salim et al, 2017;Zhou et al, 2017), and reproductive organs (Soomro et al, 2017;Huang et al, 2018) of patients infected with HEV. HEV RNA and antigens were all detectable in these replication sites and will thus facilitate studies on HEV pathogenesis and tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
“…HEV RNA was detectable in the HEV-replicated sites, including the liver, spleen, kidneys, intestines, brain, and uterus, and this result stably confirmed the extrahepatic replication sites of HEV. HEV replication has recently been identified in the kidneys (Geng et al, 2015;Pischke et al, 2017), brain (Salim et al, 2017;Zhou et al, 2017), and reproductive organs (Soomro et al, 2017;Huang et al, 2018) of patients infected with HEV. HEV RNA and antigens were all detectable in these replication sites and will thus facilitate studies on HEV pathogenesis and tissue tropism.…”
Section: Discussionmentioning
confidence: 99%
“…13 Other common predisposing microorganisms include Epstein-Barr virus, cytomegalovirus (CMV), influenza A virus, and hepatitis E virus. 14,15 In 1976, an epidemiological study showed a large increase in the incidence of GBS after swine influenza A vaccines specific to that year. 16,17 However, recent studies showed that the risk of acquiring GBS is only slightly higher after vaccination, and there is a larger benefit in reducing the occurrence of GBS after vaccination.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Among the neuro-muscular manifestations, the commonly reported were neuralgic amyotrophy (n = 102/179; 56.98%) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and Guillain-Barré syndrome (n = 36/179; 20.11%) [10,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The other rarer neurological manifestations that were reported include mononeuritis multiplex [10], encephalitis [11,13,39,41], cerebral ischemia [11,39], myasthenia gravis [42], polyneuromyopathy [24,43], meningo-radiculitis [10,44], epilepsy [11], encephalopathy [45], facial nerve palsy…”
Section: Neurological and Musculoskeletal Manifestationsmentioning
confidence: 99%